(untitled) (Research, Society and Development, 2023)
Introduction: Healthcare-associated infection (HAI), considered a nosocomial infection, is a concerning event for global public health, due to its high level of morbidity and mortality. Objective: To identify the main bacteria that cause infection in an Intensive Care Unit (ICU) and their sensitivity profiles. Methodology: Retrospective observational cross-sectional study, carried out in patients admitted to the ICU of a Teaching Hospital in the city of Cascavel - PR, in the year 2021. Results: Most patients were male (70.96%) and the microorganisms were isolated mainly from tracheal secretion 92 (49.46%). Of the total of 186 patients admitted to the ICU, 120 (64.51%) had co-infection with SARS-CoV-2, and of these, 78 (42.29%) died. Of the total of 22 species of bacteria isolated, there was a higher prevalence of Pseudomonas aeruginosa (20.22%), followed by Klebsiella pneumoniae (15.73%) and Staphylococcus aureus (9.55%). Regarding antimicrobial resistance, Pseudomonas aeruginosa showed an average of 65.37% resistance to the drugs tested, followed by Klebsiella pneumoniae (58.45%) and Staphylococcus aureus (37.05%). Conclusion: Pseudomonas aeruginosa was the main bacteria isolated, showing high resistance to drugs from the quinolones, penicillins, cephalosporins, nitrofurans and sulfonamides classes, reaching up to 100% resistance to some antimicrobials tested.